Treatment of upper aerodigestive tract cancers in England and its effect on survival - Edwards, Dympna M (Nature Publishing Group, 1999)
The evidence base for head and neck cancers is low with relatively few randomized controlled trials of the two main treatments, surgery and radiotherapy. The aim of the study was to investigate the patterns of surgery and radiotherapy treatment for head and neck cancers in three large areas of England and to investigate their effects on survival. This was a retrospective study of 13 510 cases of head and neck cancers (ICD10: C00–C14, C30–C32) diagnosed and treated from 1984 to 1992 in England. We undertook multivariate analyses of survival using a step-wise Cox proportional hazard model and Kaplan–Meier analysis. There were regional variations in the treatments given to patients. Four in ten patients did not receive currently recommended treatments. In multivariate analyses treatment content and timing had an independent effect on survival. Better survival was associated with surgery for mouth cancers, radiotherapy for laryngeal cancers and combined treatment for pharyngeal cancers independent of tumour and demographic factors. Further research is needed to investigate the findings of this study through large randomized controlled trials and multi-centre audits. © 1999 Cancer Research Campaign